A national Health and Work Strategy: a search for evidence. (5th April 2019) - Fishwick, D; Bradshaw, L; Bishop, B; Burger, M; Frost, G; Warren, N; Curran, A
Abstract: Background: The Health and Safety Executive's new Health and Work Strategy is based on an up-to-date assessment of workplace health priorities. Rather than replicating traditional prioritization approaches, a broader assessment of health and work priorities was carried out using a range of stakeholders. Aims: To develop a set of health priorities for further research and intervention activity. Methods: Four exercises were carried out, including internal prioritization, two external web-hosted questionnaire studies of younger workers and occupational health professionals, focus groups and tele-depth interviews with workplace health and safety professionals. Results: The highest rated internal priorities (weighted priority scores) were identified as mesothelioma (70), lung cancer (69.25), chronic obstructive pulmonary disease (COPD; 69), musculoskeletal disorders (MSDs; 66.25), hearing loss (65.75), stress (65.5), asthma (64.5) and hand-arm vibration syndrome (61.5). Using the three highest ranked criteria developed by occupational health professionals ((i) the preventability of the condition, (ii) the impact of the condition and (iii) the number of workers affected), mesothelioma, lung cancer, COPD, MSDs, hearing loss, stress and asthma were identified as the top seven priorities. Generic issues identified included ageing and work, obesity, newer technologies, and ethnicity and cultures of workforces. Apprentices identified stress, depression, anxiety, musculoskeletal and respiratory disorders, fatigue and workload as important workplace health considerations. Conclusions: This process identified a number of expected and new areas of health research interest. We believe the findings reflect the real world requirements of work as assessed by occupational health and safety practitioners and workers.